The Effect of prudential regulation on non-performing loans in Kenyan commercial banks - Lunani, B. (Strathmore University, 2023)
The banking sector plays an important role in the economy and its growth prospects. In 2021, total assets in the banking sector contributed to an average of 65% of Kenya’s Gross Domestic Product (GDP). The high levels of Non-Performing Loans (NPLs) in Kenya is a major concern. This study sought to ascertain the effect of bank specific aspects of prudential regulation assessed by core capital, capital adequacy, liquidity and bank stability on NPLs. The study examined the controlling effects of profitability, bank size, operational efficiency, interest rate and credit quality on NPLs. The study drew upon the capital buffer theory, credit creation theory and the financial repression theory. The study followed the positivist research philosophy and employed descriptive correlational research design. The population of the study was commercial banks operating in Kenya between 2011 and 2021. Data was analyzed using panel regression analysis According to the findings, core capital had a significant positive effect on gross NPLs implying that an increase in core capital is associated with an increase in gross NPL. There was no significant relationship between capital adequacy and liquidity on NPLs. The effect of bank stability on NPLs was significant implying that a unit increase in bank stability is associated with a reduction in gross NPL. The study findings will assist regulators in developing more efficient policies and regulations for management of NPLs. It is anticipated that banks will benefit by enhancing their credit risk management practices. By adding to the existing literature on NPLs and policy interventions, the study will contribute to advancing discussions surrounding financial markets. As a result, the general public is likely to gain enhanced confidence in the banking system and the efficacy of policy interventions.
Full- text thesis